†Japanolaccophilus beatificus sp. n. from Baltic amber and a key to the Laccophilinae genera of the World (Coleoptera: Laccophilinae) - Balke, Michael; Hendrich, Lars (Zootaxa, 2019)
We provide the first report of the subfamily Laccophilinae Gistel, 1848 from Baltic amber, based on a female specimen collected in Russia, Kaliningrad Region, Yantarnii (Jantarny) mine. This specimen represents a new species and could be assigned to the extant genus Japanolaccophilus Satô, 1972. To date this genus was monotypic with one species in Japan. The new species is here described as †J. beatificus sp. n. and compared with the extant Japanolaccophilus niponensis (Kamiya, 1939). We also provide a modified key to the Laccophilinae genera of the World, as we found minor errors or ambiguities in recent keys.